2015
DOI: 10.1038/ncomms8966
|View full text |Cite
|
Sign up to set email alerts
|

Metal-induced malformations in early Palaeozoic plankton are harbingers of mass extinction

Abstract: Glacial episodes have been linked to Ordovician–Silurian extinction events, but cooling itself may not be solely responsible for these extinctions. Teratological (malformed) assemblages of fossil plankton that correlate precisely with the extinction events can help identify alternate drivers of extinction. Here we show that metal poisoning may have caused these aberrant morphologies during a late Silurian (Pridoli) event. Malformations coincide with a dramatic increase of metals (Fe, Mo, Pb, Mn and As) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 45 publications
5
51
0
Order By: Relevance
“…The Silurian is characterized by multiple pulses of ocean anoxia and heavy metal excursions (Vandenbrouke et al. ), resulting in an unstable environment with a high degree of biotic turnover. This boom and bust macroevolution can maintain high standing diversity while the system is maintained; however, a reduction in rates can impact groups differently depending on whether they were in a boom or bust phase.…”
Section: Resultsmentioning
confidence: 99%
“…The Silurian is characterized by multiple pulses of ocean anoxia and heavy metal excursions (Vandenbrouke et al. ), resulting in an unstable environment with a high degree of biotic turnover. This boom and bust macroevolution can maintain high standing diversity while the system is maintained; however, a reduction in rates can impact groups differently depending on whether they were in a boom or bust phase.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that these signals may also be linked with the occurrence of malformed phytoplankton during early Paleozoic bioevents reported in some studies (Munnecke et al, 2012). These authors have suggested that high levels of dissolved heavy metals in the water column, including Fe 2 O 3 and Pb, may be linked to the teratological assemblages (Vandenbroucke et al, 2015). This is thought to have been driven by persistent anoxia in the deep sea and remobilization of redox sensitive elements (Emsbo et al, 2010;McLaughlin et al, 2012a).…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…The cause of these positive "excursions" in the Silurian is a matter of some debate (Saltzman, 2003;Cramer and Saltzman, 2007a;Loydell, 2007Loydell, , 2008Cramer and Munnecke, 2008;McLaughlin et al, 2012a;Vandenbroucke et al, 2015), nevertheless, it is generally thought that these phenomena are linked to widespread burial of isotopically light organic carbon ( 12 C) in the deep sea, leaving the atmosphere and hydrosphere preferentially enriched in heavy 13 C (Kump and Arthur, 1999;Saltzman and Thomas, 2012). These appear to be global phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…There are many examples of black shale deposition associated with geochemical anomalies for both the Early Palaeozoic (e.g. McLaughlin et al ., ; Vandenbroucke et al ., ) and the Late Palaeozoic (e.g. Carmichael et al ., , ; De Vleeschouwer et al ., ); as more data are acquired from a range of depositional settings, so the global nature of these events and their similarities to Mesozoic counterparts are becoming more clearly established.…”
Section: Impact Beyond the Mesozoicmentioning
confidence: 99%